2019
DOI: 10.1029/2019je006194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water on the Thermal Properties of Olivine With Implications for Lunar Internal Temperature

Abstract: How water could affect thermal transport properties is a key question that needs to be quantified experimentally when it is incorporated as structurally bound hydroxyl groups in the lattice of mantle minerals. In this study, thermal diffusivity (D) and thermal conductivity (κ) of San Carlos olivine aggregates with various water contents (up to 0.2 wt.% H2O) were measured simultaneously using transient plane‐source method up to 873 K and 3 GPa. Experimental results demonstrate that water content can significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 49 publications
(133 reference statements)
4
38
1
Order By: Relevance
“…2b for hydrogen diffusion in (Mg,Fe) 2 SiO 4 ringwoodite, the experimental data reported by Kudo et al (2006) are comparable with that calculated by the cB model (Zhang, 2012). Sun et al (2015) reported a hydrogen self-diffusion coefficient in Fe-bearing ringwood- (Hae et al, 2006); Z12 (Zhang, 2012); S18 (Sun et al, 2018); K06 (Kudo et al, 2006); K04 (Kubo et al, 2004); H09 (Holzapfel et al, 2009); S04 (Shimojuku et al, 2004); S09 (Shimojuku et al, 2009); S10 (Shimojuku et al, 2010); Z11 (Zhang et al, 2011); Z15a (Zhang and Shan, 2015a); Z15b (Zhang and Shan, 2015b); Z19b (B. H. Zhang et al, 2019b); Z21 (Zhang et al, 2021).…”
Section: Ringwooditesupporting
confidence: 72%
See 4 more Smart Citations
“…2b for hydrogen diffusion in (Mg,Fe) 2 SiO 4 ringwoodite, the experimental data reported by Kudo et al (2006) are comparable with that calculated by the cB model (Zhang, 2012). Sun et al (2015) reported a hydrogen self-diffusion coefficient in Fe-bearing ringwood- (Hae et al, 2006); Z12 (Zhang, 2012); S18 (Sun et al, 2018); K06 (Kudo et al, 2006); K04 (Kubo et al, 2004); H09 (Holzapfel et al, 2009); S04 (Shimojuku et al, 2004); S09 (Shimojuku et al, 2009); S10 (Shimojuku et al, 2010); Z11 (Zhang et al, 2011); Z15a (Zhang and Shan, 2015a); Z15b (Zhang and Shan, 2015b); Z19b (B. H. Zhang et al, 2019b); Z21 (Zhang et al, 2021).…”
Section: Ringwooditesupporting
confidence: 72%
“…However, the activation energy for O diffusion in ringwoodite reported by Shimojuku et al (2009) is inconsistent with that determined by Zhang et al (2011). (Fei et al, 2013); F14 (Fei et al, 2014); F18 (Fei et al, 2018); H05 (Hier-Majumder et al, 2005); S19 (Sun et al, 2019); Z19b (B. H. Zhang et al, 2019b); Z21 (Zhang et al, 2021).…”
Section: Ringwooditementioning
confidence: 68%
See 3 more Smart Citations